Every Start is Challenging: Fitting A New Artificial Lake Into the Landscape, Zalakaros, Hungary - Boromisza, Zsombor; Szilágyi, Ferenc; Csányi, Béla; Mészáros, Szilvia; Gergely, Attila (Journal of Environmental Geography, 2018)
The aim of this study is to conclude the experiences of the maintenance practice of an artificial thermal lake. The first years (2015-2017) of the development of the lake were analysed and evaluated along the following questions: a) What kind of design processes and maintenance interventions are related to the process of fitting the lake into the landscape? b) How have the ecological conditions of the lake evolved in the past period (zonation, succession, plantation and colonization)? c) Which general experiences could be gained from the operation of this artificial thermal lake this far? The authors of the present study were already engaged in the planning process, participating in the preparation of four different design documentations. The planting design and the maintenance instructions were based on a physico-chemical monitoring, phytoplankton, zooplankton and macroinvertebrate sampling, and machrophyte assessment. The significant processes during the three years of the lake are presented by functional groups of biota, separately assessing the characteristics of the changes of macrophytes. In 2017 an individual macroinvertebrate assessment was done, moreover a fish die-off occurred in August 2017, which are mentioned separately as well. The data in total suggested that the water of the lake is highly hypertrophic, further machrophyte introduction can prevent the plant nutriments to be absorbed by algae. Partly the algal growth but also the unlucky coincidence of other factors (e.g. high water temperature, cold weather front, maintenance problems) led to the die-off of the spontaneously overpopulated fish stock in 2017.